PENGARUH DIFUSI INOVASI LEADS UPNVJ TERHADAP KEPUTUSAN ADOPSI LEADS UPNVJ: Survey Pada Mahasiswa UPNVJ Angkatan 2021 - Abila Setiawan, (2023)
The UPNVJ LeADS program as a substitute for E-learning 4.0 which is used as a learning medium in the digital era with the application of hybrid learning requires a large adaptation process by the 2021 batch of new students as new users of the UPNVJ LeADS program itself. LeADS UPNVJ which is applied especially to UPNVJ student class of 2021 is categorized as the latest innovation because this innovation has never been done before and is new. This study aims to determine how much influence the diffusion of LeADS UPNVJ, adopter categories, and innovation characteristics of LeADS UPNVJ have on the decision to adopt LeADS UPNVJ by UPNVJ student class of 2021. The method used is an explanatory quantitative method using primary data and secondary data. The sampling technique was carried out by cluseter random sampling. Researchers conducted data analysis using eight stages, namely validity test, reliability test, assumption test, correlation analysis, multiple linear regression test, coefficient of determination test, F test, and T test. The results of the research conducted can be seen that there is a fairly strong relationship and a significant effect between the adopter category and innovation characteristics on the decision to adopt LeADS UPNVJ. The strong enough relationship means that after categorizing students into the adopter category, namely early adopters, then after students feel an ease in using LeADS UPNVJ which ultimately leads to a decision to adopt LeADS UPNVJ. The correlation test results show that there is a relationship between the LeADS UPNVJ diffusion variable and the LeADS UPNVJ adoption decision, but the relationship that occurs is in the weak category because it is at a value of 0.124 with a significance of 0.000. Then the relationship between the adopter category and the UPNVJ LeADS adoption decision, but the relationship that occurs is in a fairly strong category because it is at a value of 0.566 with a significance of 0.000. Then the relationship between innovation characteristics (X3) on UPNVJ's LeADS adoption decision (Y), but the relationship that occurs is in a fairly weak category because it is at a value of 0.485 with a significance of 0.000. Based on the results of the coefficient of determination test, the LeADS UPNVJ diffusion variable, adopter category, and innovation characteristics only contribute 47.6% to the LeADS UPNVJ adoption decision variable. Meanwhile, the other 53.4% is influenced by other factors. Based on the F test, it is known that F count is 30.045 with a significance number (P value) of 0.000. Based on the results of the hypothesis test, the t test determines the effect between the dependent variables and the dependent variable. In the UPNVJ LeADS diffusion variable (X1), Ha is rejected or means that the UPNVJ LeADS Diffusion variable (X1) has no significant effect on the UPNVJ LeADS Adoption Decision variable (Y). Furthermore, in the adopter category variable (X2), Ha is accepted or it means that the UPNVJ LeADS Adopter Category variable (X2) has a significant influence on the UPNVJ LeADS Adoption Decision variable (Y). Then on the innovation characteristics variable (X3) Ha is accepted or means that the UPNVJ LeADS innovation characteristics (X3) have a significant influence on the UPNVJ LeADS Adoption Decision variable (Y).